Flexibility-Oriented Day-ahead Market Clearing Model for Electrical Energy and Ancillary Services - Meng YANG; Lizi ZHANG; Jianhu LV; Bike XUE; Hao YUAN (Zhongguo dianli)
In the power system with high penetration rate of renewable energy, the day-ahead market of electric energy and ancillary services acts as the primary trading platform to support the short-term operation flexibility of the power system. Therefore, its market clearing model is of vital importance for the effective incentive and utilization efficiency of flexible resources. In this paper, combined with the system demand for flexible power resources, the influence of traditional unit commitment model on the utilization efficiency of flexible resources is analyzed, and a flexible day-ahead market co-optimization model is then proposed. The model incorporated the ramping variables into the decision variables, and took into account the effects of the unit start-stop process output, optimal time interval, ancillary service adjustment direction and other factors on the system flexibility, so as to achieve the joint clearing of different trading varieties. Case studies on the system including renewable energy, nuclear power and energy storage indicates that the application of this method exhibits the performance differences of various flexible resources and hence better meet the needs of high-proportion renewable energy systems.